Improving clean‐catch contamination rates: A prospective interventional cohort study. (24th October 2016) - Teo, Sharon; Cheek, John A; Craig, Simon
Abstract: Objectives: The clean‐catch method of urine collection carries a high contamination rate. This study aims to evaluate the effects on contamination rate of providing a parent handout and pre‐made urine collection pack for clean‐catch urine collection. Methods: We conducted a single‐centre prospective cohort interventional study in a tertiary paediatric ED. All children younger than 24 months who presented from April 2013 to June 2014 requiring a urine sample to be obtained were included. The intervention was provision of a pre‐made urine collection pack including a standardised information handout. The primary outcome measure was the difference in proportion of urine contamination in samples obtained via a clean‐catch pre‐ and post‐intervention. Results: The total number of urine specimens included was 288 in the pre‐intervention group and 333 in the post‐intervention group. Contamination rates were 14.9% in the pre‐intervention group and 11.4% in the post‐intervention group. There was no statistically significant reduction in contamination ( P = 0.19). The contamination rates appeared to be associated with gender, with (pooled) female contamination rates being 16.4% (44/269) and male contamination rates being 10.5% (37/352). Most specimens of urine were collected via the clean‐catch method (81.2%), followed by catheter urine specimen (13.7%) and suprapubic aspirate (5.1%). The contamination rate in our study for clean‐catch urine collectively was 13%, catheter urine specimen 3.8% and suprapubic aspirate 0%. Conclusion: The contamination rate of clean‐catch urine did not improve with the implementation of a pre‐made urine collection pack including standardised written instructions.